The Philosophy of Pancasila as The Grand Theory of Legal Research Based on Bibliometric Analysis - Martin Roestamy; Abraham Yazdi Martin; Radif Khotamir Rusli (Universitas Djuanda, 2022)
Grand Theory is a prominent theory in macro to explain social life, history, and human experience. The research purpose is to find a mapping analysis with the VOSviewer application to carry out a bibliometric analysis of research in law. Research data was obtained through Publish or Perish software. The information data collected is the search result for the terms